2014
DOI: 10.1021/np401047w
|View full text |Cite
|
Sign up to set email alerts
|

Aspewentins A–C, Norditerpenes from a Cryptic Pathway in an Algicolous Strain of Aspergillus wentii

Abstract: Through addition of suberoylanilide hydroxamic acid, two new aromatic norditerpenes, aspewentins A (1) and B (2), along with an oxygenated derivative, aspewentin C (3), were obtained from the culture of an Aspergillus wentii strain (na-3) isolated from the tissue of the brown alga Sargassum fusiforme. The structures and absolute configurations were unambiguously elucidated by spectroscopic analyses and quantum chemical calculations. Aspewentins A-C were produced before sporulation and exhibited potent bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 17 publications
2
53
0
2
Order By: Relevance
“…The 13 C NMR data (Table 2) revealed the presence of 19 carbon signals, and were classified into three methyls, six methylenes (with one olefinic), three methines (with one oxygenated and two olefinic), and seven quaternary carbons by DEPT and HSQC experiments. A detailed analysis of the 1D NMR data revealed that 1 might be a 14-hydroxylated derivative of aspewentin C, a 20-nor-isopimarane diterpenoid identified from the algicolous strain A. wentii na-3 [6]. The observed HMBC correlations (Figure 2) from H-14 to C-7, C-9, and C-12 supported this conduction.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The 13 C NMR data (Table 2) revealed the presence of 19 carbon signals, and were classified into three methyls, six methylenes (with one olefinic), three methines (with one oxygenated and two olefinic), and seven quaternary carbons by DEPT and HSQC experiments. A detailed analysis of the 1D NMR data revealed that 1 might be a 14-hydroxylated derivative of aspewentin C, a 20-nor-isopimarane diterpenoid identified from the algicolous strain A. wentii na-3 [6]. The observed HMBC correlations (Figure 2) from H-14 to C-7, C-9, and C-12 supported this conduction.…”
Section: Resultsmentioning
confidence: 76%
“…Aspergillus wentii is a biosynthetically talented fungal species with great potential to produce a wide range of structurally diversified secondary metabolites such as glucans [1], polyketides [2,3], and terpenoids [4,5,6]. Some of these metabolites exhibit intriguing biological properties including antimicrobial properties [2,6], antioxidant properties [3], cytotoxicity against human cancer cell lines [5], and plant growth-inhibiting activities [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, over 20% were obtained from marine algicolous fungi, including endophytic and epiphytic strains (Rateb & Ebel 2011). The marine alga-derived endophytic fungi were the focus of our researches, and a series of new terpenes, steroids, polyketides and alkaloids have been isolated and identified (Miao, Li, et al 2012;Miao, Liang, et al 2012;Ji et al 2013;Liu et al 2013;Sun et al 2013;Miao et al 2014). Trichoderma species were known for the production of functional products (Ahluwalia et al 2015;iqtedar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical calculations greatly expand the application of these techniques. Using these techniques and computational calculations, a series of structurally interesting compounds have been discovered from marine algae and algicolous fungi (Li et al, 2013;Ji et al, 2013;Miao et al, 2014). The aim of the present study was to investigate the alga-endophytic fungus Talaromyces sp.…”
Section: Introductionmentioning
confidence: 99%